2009
DOI: 10.2174/092986709789878292
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacomimetics of Exercise: Novel Approaches for Hippocampally- Targeted Neuroprotective Agents

Abstract: Coordinated and constructive physical activity is correlated with the maintenance of cognitive function in humans. Voluntary running also enhances neuroplasticity in adult and aging rodents, but the molecular pathways underlying these effects are still being elucidated. Considering the multifactorial nature of the biochemical links between physical activity and neurophysiology it is likely that there are many pharmacological mechanisms by which the beneficial actions of exercise can be effectively reproduced u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 103 publications
(137 reference statements)
3
37
0
Order By: Relevance
“…Voluntary exercise restored both the capacity of neuronal counting and the performances in the water maze test. Our finding is consistent with previous results showing that exercise enhances learning and memory capability through stimulating hippocampal neurogenesis leading to enhance learning and memory capability (9,10,12,14,18,23,24).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Voluntary exercise restored both the capacity of neuronal counting and the performances in the water maze test. Our finding is consistent with previous results showing that exercise enhances learning and memory capability through stimulating hippocampal neurogenesis leading to enhance learning and memory capability (9,10,12,14,18,23,24).…”
Section: Discussionsupporting
confidence: 93%
“…In line with our study, it was shown that the hippocampal DG (as a source of neural stem cells) continues to generate new neurons throughout the lifespan, and physical activity also causes an increase in neurogenesis in the DG of the hippocampus, a brain area important for learning, memory (10), and synaptic plasticity (17). Our finding is consistent with previous results showing that exerciseassociated changes in synaptic plasticity occurred in the same region where neurogenesis occurred by running, suggesting that newborn cells have a functional role in this process (9).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations